Analisis Objektif Terhadap Karya Sastra “Padamu Jua” Karya Amir Hamzah - Mutika Zahrah (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2024)
The poem "Padamu Jua" by Amir Hamzah expresses deep longing, inner struggle and spiritual search. This research analyzes the poem using an objective approach to intrinsic elements, including theme, structure, symbolism and language style. The main theme of this poem is spiritual longing and a sense of loss. The free structure of the poem reflects the poet's emotional turmoil, while symbolism such as the candlestick, lamp, and claws provide deep meaning regarding hope, enlightenment and the complexity of human relationships with love or God. The use of language styles such as metaphor, personification and repetition strengthens the emotional message and intensity of longing conveyed. This poem reflects the struggle to find peace amidst the emptiness of worldly love. It is hoped that this research can provide a new understanding of the meaning and aesthetics of Indonesian classical literary works.